2018
DOI: 10.3390/met8100774
|View full text |Cite
|
Sign up to set email alerts
|

Phase Equilibria in the Ni-V-Ta Ternary System

Abstract: Two isothermal sections of the Ni-V-Ta ternary system at 1200 °C and 1000 °C have been experimentally established using X-ray diffraction, electron probe microanalysis, energy dispersive spectroscopy, and differential scanning calorimeter with equilibrated key alloys. The equilibrium composition of each phase is measured by electron probe microanalysis and energy dispersive spectroscopy. The results indicate that: (1) nine three-phase and eight three-phase regions were confirmed in the isothermal section at 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Thus, in their thermodynamic modeling, the C14 existed in two temperature regions, that is, from 0 to 626 K and from 1409 to 1703 K. Later, the measurements from Khan et al [ 58 ] indicated that C14 was not found in four Ta-V alloys, which were annealed at 1473 K for 15 days. However, the recent phase equilibrium investigations in ternary Ta-V-Ni [ 59 ] and Ta-V-Co [ 60 ] systems displayed that the C14 phase existed in the Ta-V side at 1473 and 1573 K but was not found at 1173, 1273 and 1373 K after long-time annealing. Since no further experimental data confirm the existence of C14 below 626 K, as proposed by Pavlů et al [ 56 ], the phase relationship between C14 and C15 recommended by Danon and Servant [ 55 ] was adopted in the present modeling.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, in their thermodynamic modeling, the C14 existed in two temperature regions, that is, from 0 to 626 K and from 1409 to 1703 K. Later, the measurements from Khan et al [ 58 ] indicated that C14 was not found in four Ta-V alloys, which were annealed at 1473 K for 15 days. However, the recent phase equilibrium investigations in ternary Ta-V-Ni [ 59 ] and Ta-V-Co [ 60 ] systems displayed that the C14 phase existed in the Ta-V side at 1473 and 1573 K but was not found at 1173, 1273 and 1373 K after long-time annealing. Since no further experimental data confirm the existence of C14 below 626 K, as proposed by Pavlů et al [ 56 ], the phase relationship between C14 and C15 recommended by Danon and Servant [ 55 ] was adopted in the present modeling.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, in their thermodynamic modeling, the C14 existed in two temperature regions, that is, from 0 to 626 K and from 1409 to 1703 K. Later, the measurements from Khan et al [58] indicated that C14 was not found in four Ta-V alloys, which were annealed at 1473 K for 15 days. However, the recent phase equilibrium investigations in ternary Ta-V-Ni [59] and Ta-V-Co [60] systems displayed that the C14 phase existed in the Ta-V side at 1473 and 1573 K but was not found at 1173, 1273 and 1373 K after long-time annealing. Since no further experimental data confirm the existence of C14 below 626 K, as proposed by Pavl ů et al [56], the phase relationship between C14 and C15 recommended by Danon and Servant [55] was adopted in the present modeling.…”
Section: Thermodynamic Descriptions Of Ta-cr and Ta-v Binary Systemsmentioning
confidence: 96%